Merry Christmas mom and dad - Mayer, Mercer, 1943- (Western Pub. Co., 1982)
Trying to be good for Christmas without bungling everything up is difficult.
On t.p. "Kris" is printed as a lined-out word replaced by "Christmas."
1 4 6 7 11 13 17 21 25 26 27 29 30 39
Keywords: Christmas -- Fiction